Vitamin A deficiency, a potential threat to sight in transplant recipients - Fatema Ali Lanewala (Journal of the Pakistan Medical Association, 2023)
Vitamin A (Vit A or Retinol) is an essential nutrient for proper human body functioning including embryogenesis, vision, cell proliferation and differentiation, immune regulation, and glucose and lipid metabolism. It is mainly acquired through diet rich in Retinol or Retinyl esters; or its precursors like carotenoids, Provitamin A, and beta carotene.1,2 Continue...